Effects of supercritical CO2 on micropores in bituminous and anthracite coal. (15th April 2019) - Liu, Shiqi; Sang, Shuxun; Ma, Jingsheng; Wang, Tian; Du, Yi; Fang, Huihuang
Highlights: Investigating the effects of scCO2 on micropores in coals of different ranks. Identifying the effects of scCO2 on chemical structure and organic groups of coals. The coal rank has a positive influence on the micropore volume. Abstract: The effects of supercritical CO2 (ScCO2 ) on coal micropores play a critical role in determining the CO2 capacity of coalbeds. To investigate the effects of ScCO2 on micropores in coals of different ranks under a range of temperature and pressure conditions, CO2 sequestration processes are replicated using a ScCO2 geochemical reactor. Four samples of coal of different ranks are exposed to ScCO2 and water for 240 h at 62.5 °C and 15 MPa, and CO2 adsorption tests, Fourier transform infrared spectroscopy, and X-ray diffraction are performed to determine the volume and pore size distribution of the micropores, the types and contents of the organic groups, and the aromatic crystallite structures of the coal samples before and after the ScCO2 -H2 O treatment. The influence of the chemical structure and the organic groups of the coal on the coal micropores is then studied. Micropores with widths <0.46 nm are mainly associated with the inter-layer spacing of the aromatic layers. Swelling caused by ScCO2 detaches heterocycles and non-condensed polynuclear aromatics of high-volatile bituminous coal, resulting in slight increases in the volume of micropores with widths <0.46 nm. The falling off of cross-links with low bond energies caused by swelling and the formation of CAr CAr cross-links between the aromatic layers caused by polyaddition reactions together cause a decrease in the volume of micropores with widths <0.46 nm in semi-anthracite and anthracite coal. Micropores with widths >0.46 nm are pores in the macromolecular structure of coal and are known as intermolecular pores, and their volumes are determined by the directional arrangement of aromatic crystallites and the aliphatic hydrocarbon chain length. The broken bonds caused by ScCO2 in high-volatile bituminous coal form new aliphatic or aromatic compounds via addition and polyaddition reactions. These processes increase the directional arrangement of aromatic crystallites, resulting in a decrease in the volume of micropores with widths >0.46 nm. As the coal rank increases, the aliphatic hydrocarbon chain length gives priority to the macromolecular structure of coal after the ScCO2 treatment, resulting in an increase in the volume of micropores with widths >0.46 nm in semi-anthracite and anthracite coal.